Assessment of Pollution and Improvement Measure of Water Quality Parameters using Scenarios Modeling for Sungai Selangor Basin - Chowdhury, Md Sadek Uddin; Othman, Faridah; Wan Jaafar, Wan Zurina; Mood, Nuzaima Che; Adham, Md Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2018)
Sungai Selangor is very important from the viewpoint of water supply and multipurpose water use in Malaysia. The water quality of this river is degrading due to point and non-point sources of pollution. This study, focus on the water quality assessment and simulation the effect of the pollution sources from urbanization to the Sungai Selangor basin. Water quality Index (WQI) is used to define the status of river water quality and the QUAL2K was used as a simulation model. Water quality parameters DO, BOD and NH3-N have been chosen for modeling. In addition, five different model scenarios were simulated to observe the impacts of pollution sources on the Sungai Selangor water quality. WQI results showed that most of the stations in this river basin recorded water inferior to Class III. The water quality model presented different scenarios for changes of Sungai Selangor water quality. Simulation results for different scenarios showed that reduced levels of BOD and NH3-N at 51.10% and 66.18%, respectively, can be obtained if Scenario-5 is employed. The river water quality issue in the Rawang sub- basin within the study area is considered crucial to create significant improvement within the sub basin and in the downstream area of Sungai Selangor basin.